Market response to bank relationships: Evidence from Korean bank reform - Sohn, Wook (Journal of Banking & Finance, 2010)
This paper examines how the forced closure of failing banks and the transfer of their loans to surviving banks affect the market value of firms that borrow from the closed banks. Pre-existing relationships between firms and the banks that acquire their loans are detrimental to the positive valuation effects of the event. Banks may have an incentive to favor pre-existing relationships to increase the value of previously extended loans. Therefore, loan renewals to firms with prior relationships do not signal borrower quality to the market, which is aware of the banks’ conflicts of interest. This study highlights the importance of the specific mechanisms employed to replace failed banks without decreasing the value of their client firms.